Single-Copy Genes as Molecular Markers for Phylogenomic Studies in Seed Plants. (1st May 2017) - Li, Zhen; De La Torre, Amanda R.; Sterck, Lieven; Cánovas, Francisco M.; Avila, Concepción; Merino, Irene; Cabezas, José Antonio; Cervera, María Teresa; Ingvarsson, Pär K.; Van de Peer, Yves
Abstract : Phylogenetic relationships among seed plant taxa, especially within the gymnosperms, remain contested. In contrast to angiosperms, for which several genomic, transcriptomic and phylogenetic resources are available, there are few, if any, molecular markers that allow broad comparisons among gymnosperm species. With few gymnosperm genomes available, recently obtained transcriptomes in gymnosperms are a great addition to identifying single-copy gene families as molecular markers for phylogenomic analysis in seed plants. Taking advantage of an increasing number of available genomes and transcriptomes, we identified single-copy genes in a broad collection of seed plants and used these to infer phylogenetic relationships between major seed plant taxa. This study aims at extending the current phylogenetic toolkit for seed plants, assessing its ability for resolving seed plant phylogeny, and discussing potential factors affecting phylogenetic reconstruction. In total, we identified 3, 072 single-copy genes in 31 gymnosperms and 2, 156 single-copy genes in 34 angiosperms. All studied seed plants shared 1, 469 single-copy genes, which are generally involved in functions like DNA metabolism, cell cycle, and photosynthesis. A selected set of 106 single-copy genes provided good resolution for the seed plant phylogeny except for gnetophytes. Although some of our analyses support a sister relationship between gnetophytes and other gymnosperms, phylogenetic trees from concatenated alignments without 3rd codon positions and amino acid alignments under the CAT + GTR model, support gnetophytes as a sister group to Pinaceae. Our phylogenomic analyses demonstrate that, in general, single-copy genes can uncover both recent and deep divergences of seed plant phylogeny.